Mitochondria: the Headquarters in Ischemia-Induced Neuronal Death - Jordan, Joaquin; W.J. de Groot, Piet; F. Galindo, Maria (Central Nervous System Agents in Medicinal Chemistry, 2011)
Due to a lack of efficient treatments, searching for novel therapies against acute ischemic stroke represents one of the main fields in neuropharmacology. In this review we summarize and discuss the role of mitochondrial participation in ischemia-induced neuronal death. Mitochondria are regarded as the main link between cellular stress signals and the execution of programmed death of nerve cells. Since it was described that the release of mitochondrial proteins such as cytochrome c, apoptosis inducing factor and endonuclease G are key elements in cell death pathways, they have been the focus of cell death studies. Changes in the permeability of the mitochondrial outer membrane result in a non-reversible step in cell death processes. Cytochrome c released from mitochondria binds in the cytoplasm to Apaf-1 to initiate the formation of an apoptosome, which then binds pro-caspase-9. Active caspase-9 cleaves “executioner” caspases, which in turn proceed to cleave key substrates in the cell. Thus, the identification of new targets might enable establishment of novel strategies for therapeutic research, in this case based on the molecular mechanisms of mitochondrial pathways, to improve the development of compounds for treatment of ischemia.
Keywords: Treatment